2019
DOI: 10.1161/hypertensionaha.118.12286
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Role of T Cells and IL-6 (Interleukin-6) in Angiotensin II–Induced Microvascular Dysfunction

Abstract: Hypertension (HTN) is an established risk factor for subsequent cardiovascular diseases, with Angiotensin II (Ang-II) playing a major role in mediating thrombotic and inflammatory abnormalities. Although T cells and interleukin-6 (IL-6) play an important role in adaptive immune responses, little is known about their role(s) in the thrombo-inflammatory responses associated with Ang-II. Here we show using intravital microscopy coupled with the light/dye injury model that Rag-1 deficient (Rag-1 −/−) and IL-6 defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 58 publications
2
48
0
2
Order By: Relevance
“…A previous study revealed that IL-6 could mediate thrombocytosis, platelet hyperreactivity, and accelerate extra-intestinal thrombosis associated with experimental colitis [11]. Another study showed that IL-6 and T-cell-dependent IL-6 signaling was involved in angiotensin II-induced thromboin ammation [12]. As one of the most important members in the coagulation system, tissue factor could also mediate the production of pro-in ammatory cytokines by activating protease-activated receptors on various cells such as mononuclear cells, endothelial cells, platelets, and so on [13].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that IL-6 could mediate thrombocytosis, platelet hyperreactivity, and accelerate extra-intestinal thrombosis associated with experimental colitis [11]. Another study showed that IL-6 and T-cell-dependent IL-6 signaling was involved in angiotensin II-induced thromboin ammation [12]. As one of the most important members in the coagulation system, tissue factor could also mediate the production of pro-in ammatory cytokines by activating protease-activated receptors on various cells such as mononuclear cells, endothelial cells, platelets, and so on [13].…”
Section: Introductionmentioning
confidence: 99%
“…There is also accelerated microvascular thrombosis in arterioles and to a lesser extent in venules after Ang II infusions. 53 Clinical data also support the role of Ang II in fibrinolysis. Plasminogen activator inhibitor 1 (PAI-1) is the major inhibitor of the fibrinolytic system and elevated levels have been found to be associated with coronary artery disease, deep vein thrombosis, and malignancy.…”
Section: The Role Of Angiotensin IImentioning
confidence: 85%
“…IL-6 upregulates cathepsin L production 4 , which then cleaves the virus, enabling it to infect pulmonary epithelial cells 3 . IL-6 also upregulates the Angiotensin II AT1 receptor 17 , and likely upregulates pulmonary epithelial cell ACE2 receptors, with a positive correlation between IL-6 and ACE2 levels in bronchioalveolar lavage (BAL) in patients with severe acute pulmonary in ammation 5 . Viral reproduction within pulmonary epithelial cells then recruits in ammatory cells which, in turn produce cytokines (as part of the "cytokine storm" phenomenon 18 ) including IL-6.…”
Section: Discussionmentioning
confidence: 99%